Manju Kapur’s ‘Home’: A Strong Voice of Protest - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education, 2021)
Women’s issues in India are different from those in the western countries where a woman’s quest for identity and survival become major discourses. Writers who are conscious of the “othering” of women need to make ordinary women understand the possibility of power, of being able to control their own lives, and to have this power, not as mothers, not as devoted wives, but as ordinary women. But, Indian women writers have to first battle against the deeply ingrained critical prejudices that writing is an activity which belongs exclusively to men and if a woman writes at all, it is always a futile exercise. Manju Kapur’s ‘Home’ is a feminist discourse not only because the novelist is a woman writing about women but also because she understands women’s minds. How to cite this article: Priydarshi AK. Manju Kapur’s ‘Home’: A Strong Voice of Protest. J Adv Res Eng & Edu 2021; 6(3): 3-5. DOI: https://doi.org/10.24321/2456.4370.202105